Developing QuizWhizzer-Based Learning Evaluation for Fictional Text Materials in Elementary School - Srikandi, Sindy; Fakhrunnisaa, Nur; Aswar, Nurul (Journal of Indonesian Islamic Studies, 2024)
This study aimed to develop QuizWhizzer-based learning evaluation for fictional text materials in elementary school. The study employed a Research and Development (R&D) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research was conducted at SD Negeri 54 Salupikung involving one classroom teacher and 16 sixth-grade students. Data were collected through observation, interviews, questionnaires, and documentation. The developed product was validated by media experts, material experts, and language experts, while practicality data were obtained through teacher and student response questionnaires. The results showed that the QuizWhizzer-based learning evaluation obtained an average validity score of 87% and was categorized as very valid. The practicality test results indicated that student responses reached 95.8% and teacher responses reached 94%, both categorized as very practical. In addition, the average student evaluation score reached 87.5, with 15 students achieving the minimum mastery criteria. These findings indicate that the QuizWhizzer-based learning evaluation is valid and practical for use in Indonesian language learning, particularly for fictional text materials in elementary school. Therefore, QuizWhizzer can be used as an alternative digital evaluation media to support interactive and engaging learning evaluation processes in elementary education.